Diagnosis of tuberculous peritonitis using endoscopic ultrasound-guided fine-needle aspiration biopsy of the peritoneum - Orhan Kocaman; Ahmet Danalıoğlu; Ali Tüzün İnce and Mukaddes Tozlu and Hakan Şentürk (Turkish Journal of Gastroenterology, 2019)
-